1999
DOI: 10.1053/joca.1998.0152
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of radiographic assessment in hip and knee osteoarthritis

Abstract: A reliable radiographic severity grading of hip and knee OA is possible with the application of global scores and individual features, if joint specific items are selected and readers are trained enough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 0 publications
6
62
1
1
Order By: Relevance
“…Using conventional radiography, intrareader reliability for assessment of knee osteoarthritis features has been reported to be lower for less experienced readers in general, even after receiving intensive training, compared to a more experienced reader (23). The same trend was observed in the present study for the tomosynthesis assessment of osteophytes, but not for subchondral cysts.…”
Section: Discussionsupporting
confidence: 80%
“…Using conventional radiography, intrareader reliability for assessment of knee osteoarthritis features has been reported to be lower for less experienced readers in general, even after receiving intensive training, compared to a more experienced reader (23). The same trend was observed in the present study for the tomosynthesis assessment of osteophytes, but not for subchondral cysts.…”
Section: Discussionsupporting
confidence: 80%
“…The intraobserver and interobserver reliability of these systems reportedly ranges from 0.18 to 0.95 [18,19,32,44]. We found that the modified Kellgren-Lawrence, Takakura et al, and van Dijk et al grading systems had reliability ranging from 0.51 to 0.89.…”
Section: Discussionmentioning
confidence: 65%
“…As a result of the focus on osteophytes and the assumption that OA would result in joint space narrowing with the Kellgren-Lawrence grading system, other grading systems have been developed [18,19,32,44,47]. The intraobserver and interobserver reliability of these systems reportedly ranges from 0.18 to 0.95 [18,19,32,44].…”
Section: Discussionmentioning
confidence: 99%
“…This technique has a large intra-user and inter-user variability [3] and relies on a single image to represent the whole joint. The use of a semiautomated computer algorithm can overcome the variability related to manual measurements [4], while the use of MRI can lead to a more precise tracking of the disease.…”
Section: Introductionmentioning
confidence: 99%